PERAN MEDIA SOSIAL UNTUK MENINGKATKAN JANGKAUAN PEMASARAN DAN NILAI EKONOMI PADA USAHA “LILIN AROMATHERAPY” HASIL DARI WIRAUSAHA MERDEKA - Putra, Fahreza Nandito (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study explores the role of social media in expanding the marketing reach of the "Lilin Aromatherapy" business within the context of digital technology development. The use of social media platforms such as Instagram and WhatsApp has proven effective in increasing followers and content views, contributing to enhanced brand awareness and sales. This research employs qualitative methods, collecting data from social media content and interviews with business members. The findings indicate that digital marketing strategies, including personal selling promotions at Car Free Day (CFD) events and regular social media publications, successfully attract public interest. Analysis shows that direct discounts are more effective than buy-three-get-one-free promotions. Regular publications with informative and engaging content on social media can expand market reach and enhance customer loyalty. This study highlights the importance of integrating digital technology into business strategies to achieve sustainable growth and increase the economic value of small and medium-sized enterprises in the digital era.